Reconstructing past sea-level changes from storm-built beach ridges - Rovere, Alessio (2025)
Storm-built beach ridges, built by waves on sedimentary coasts, can be used as geomorphological indicators of past sea level. However, quantifying the relationship between the geomorphological elements of the ridge and the paleo sea level at the time of deposition is difficult, as a beach ridge is primarily correlated to wave energy and only secondarily to the position of sea level. In this work, we propose a methodology to quantify the upper and lower limits of a storm-built beach ridge based on remote sensing data. We use the tidal model FES2022, data from the Copernicus Marine Service and beach slope gathered from satellite imagery as inputs to different wave runup models, that are used to calculate the limits of the storm-built beach ridge. We test our approach on a particularly well-preserved Pleistocene storm-built beach ridge in Patagonia, Argentina. Our results show that the paleo relative sea level reconstructed using remote sensing data coincides (82.8 % similarity) with that obtained from measured modern analog landforms at the same location.